2014
DOI: 10.1177/1938640014528973
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Static Pressure Distribution in Healthy Individuals

Abstract: Diagnostic Level IV: Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…Hence, in the current study no leg differences between sexes in plantar load distribution were detected. Our study is in good agreement with data presented by Pomarino and Pomarino [ 33 ] where no significant differences between legs in both sexes were reported.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Hence, in the current study no leg differences between sexes in plantar load distribution were detected. Our study is in good agreement with data presented by Pomarino and Pomarino [ 33 ] where no significant differences between legs in both sexes were reported.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with those of da Rocha et al [ 27 ] confirming that, independently of weight category, rearfoot was the foot region with highest pressure distribution. Furthermore, depending on the internal and external factors, the pattern of weight distribution in different regions of the foot has been investigated and, generally, it has been reported that certain factors, [ 33 , 34 ] and specifically among children with postural deformities, [ 35 ] and different diseases, [ 36 ] as well as sport specificity [ 37 ] might determine the region of the foot which is loaded with greater plantar pressure distribution. Indeed, previous studies have reported an age effect in plantar pressure distribution in different foot regions among healthy children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not observed in the experimental group, which may indicate that after training with the exoskeleton, load distribution within the limbs was better than after classical rehabilitation. As was reported, the appropriate load distribution should be 33% of backfoot load and 66% of forefoot load (27). In addition, as a result of training with the exoskeleton, patients significantly increased walking distance and the number of steps performed during a training unit.…”
Section: Discussionmentioning
confidence: 90%
“…So far, though, only a few studies have dealt specifically with the sex of the subjects [ 9 ], [ 13 , 14 ], whereas other authors [ 15 – 17 ] have collected posturographic parameters in heterogeneous subject groups:…”
Section: Introductionmentioning
confidence: 99%